Smart archive management: The interplay of organizational culture and knowledge governance - Amaliyah, Amaliyah; Sahlimar, Nadiya Sahwa; Dimisyqiyani, Erindah; Pertiwi, Ajeng Rachma; Putri, Eka Lestari Hafqi; Abdullah, Siti Intan Nurdiana Wong (Record and Library Journal, 2025)
Background of the study: This study investigates the implementation of innovative archive management by examining the interaction between organizational culture and knowledge governance within the Surabaya City Library and Archives Office. As public institutions move toward data-driven and innovative information environments, understanding how cultural and governance structures support technological adaptation becomes essential. Purpose: This study investigates the implementation of innovative archive management by examining the interaction between organizational culture and knowledge governance within the Surabaya City Library and Archives Office. Method: Employing a quantitative survey method with purposive sampling, data were collected from 120 employees who had served for more than one year. The data were analyzed using SmartPLS to test both direct and mediating relationships. Findings: The results reveal that innovative archive management significantly enhances the quality, accessibility, and security of digital records. Moreover, organizational culture and knowledge governance play crucial roles in reinforcing innovation, collaboration, and compliance in archival processes. Conclusion: These findings emphasize that successful digital transformation in public-sector archiving requires not only technological readiness but also cultural adaptability and effective knowledge-governance mechanisms to ensure sustainable institutional learning and accountability.